Prevalence of Hepatitis B & C Viruses among Patients in Dialysis Centers in Zintan and Yefren Cities, Libya - Abubakeer, Adell; Alfaqi, Rahma; Alhagig, Elham; Mariam Ali; Alfliow, Ziad (AlQalam Journal of Medical and Applied Sciences, 2025)
Patients on hemodialysis face a higher risk of viral hepatitis due to factors like frequent blood transfusions, prolonged vascular access, and exposure to infected patients and equipment. These issues pose significant challenges for healthcare systems, especially in developing countries. This study aimed to assess the prevalence of HBV and HCV among hemodialysis patients in Zintan and Yefren, Libya. In this study, 87 serum specimens were collected from hemodialysis patients, 47 men and 40 women, between February and May 2024. The samples were tested for hepatitis B surface antigen (HBsAg) and HCV antibodies using ELISA. Results showed a low prevalence; HBsAg was positive in 1.14% (1 out of 87), and anti-HCV antibodies were also detected in 1.14% (1 out of 87). While the low prevalence suggests a reduced risk in these facilities, further research on demographic and clinical risk factors is needed. In conclusion, the prevalence of HBV and HCV among hemodialysis patients in this region is reassuringly low, indicating effective management practices. يواجه المرضى الذين يخضعون لغسيل الكلى خطرًا للإصابة بالتهاب الكبد الفيروسي بسبب عوامل مثل عمليات نقل الدم المتكررة، والتعرض للمرضى المصابين والمعدات وغيرها. تشكل هذه القضايا تحديات كبيرة لأنظمة الرعاية الصحية، وخاصة في البلدان النامية. هدفت هذه الدراسة إلى تقييم انتشار التهاب الكبد الفيروسي ب والتهاب الكبد الفيروسي سي بين مرضى غسيل الكلى في مركز الغسيل في الزنتان ويفرن، ليبيا. في هذه الدراسة، تم جمع 87 عينة مصل من مرضى غسيل الكلى، 47 رجلاً و40 امرأة بين فبراير ومايو 2024. تم اختبار العينات بحثًا عن مستضد سطح التهاب الكبد ب (HBsAg) والأجسام المضادة لفيروس التهاب الكبد سي باستخدام تقنية المقايسة المناعية المرتبطة بإلنزيم (ELISA). أظهرت النتائج انتشارًا منخفضًا، وكان مستضد سطح التهاب الكبد ب إيجابيًا بنسبة 1.14٪ (1 من أصل 87) وتم الكشف عن أجسام مضادة لفيروس التهاب الكبد سي أيضًا بنسبة 1.14٪ (1 من أصل 87). في حين يشير الانتشار المنخفض إلى انخفاض المخاطر في هذه المرافق، إلا أن هناك حاجة إلى مزيد من البحث حول عوامل الخطر الديموغرافية والسريرية. وفي الختام، فإن معدل انتشار التهاب الكبد الفيروسي ب و ج بين مرضى غسيل الكلى في هذه المنطقة منخفض بشكل مطمئن، مما يشير إلى ممارسات إدارة فعالة